Financing the African Colonial State: The Revenue Imperative and Forced Labour - Marlous van Waijenburg (African Economic History Network (AEHN), 2015)
Recent studies on colonial public finance have pointed to the severe constraints to fiscal capacity building Sub-Saharan Africa, and to the inclination of colonial governments to avoid direct taxes when revenue from trade became sufficiently available. Although fiscal revenue was indeed a central pillar of the colonial state formation process, contributions from a widely used but implied source of government 'income' – that of forced labor (or 'labor taxes') – have so far been left out of the picture. Exploiting data on labor corvée schemes in French Africa between 1913-1937 (the prestations), this is the first paper to provide estimates of how much this in-kind form of revenue may have enhanced colonial budgets. I show that in most places labor taxes constituted the most important component of early colonial state income. My results imply that studies on historical fiscal capacity building efforts need to make a greater effort to estimate and integrate this significant source of state income into their analysis.
Keywords: N27; N37; N57; 330; Taxation; Labor Coercion; Africa; Colonial Institutions